Changes in Self-Reported Fruit and Vegetable Intake following Nutritional Modification in High Risk Older Veterans. Issue 1 (2nd January 2021) - Serra, Monica C.; Addison, Odessa; Giffuni, Jamie; Barton-Ort, Kelly; Parker, Elizabeth; Katzel, Leslie
Abstract: This project aimed to determine the feasibility of implementing a dietary intervention in older Veterans participating in an exercise and health promotion program (Gerofit) and whether this intervention could improve self-reported fruit and vegetable (F&V) intake measured by BRFSS and diet quality measured by visual analog scale (0–10 scale). Participation consisted of optional group and individual counseling with a Registered Dietitian (RD). Out of 50 participants approached to participant in the program, 24 Veterans attended ≥2 group sessions (2.9 ± 2.0 classes, which was 82% of total available sessions). There was a reported trend toward increased daily F&V intake (pre vs. post: 3.4 ± 1.9 vs. 4.1 ± 2.0 servings/day, p = 0.07) and a significant increase in diet quality (4.7 ± 0.5 vs. 5.9 ± 0.4, p = 0.03) from baseline compared to the last attended class. These promising preliminary findings can be used to inform efforts to optimize dietary intake in vulnerable Veteran populations.